A Powerful and Universal Preimplantation Genetic Diagnosis Protocol for Cystic Fibrosis - Victoria Viart; Aliya Ishmukhametova; Stéphanie Plaza; Garance Verrière; Florielle Saguet; Mireille Claustres; Anne Girardet (European Medical Journal, 2018)
Background: Cystic fibrosis (CF) is one of the most common indications of preimplantation genetic diagnosis (PGD) for monogenic disorders worldwide. Aims: The aim of this article was to report a universal and powerful assay easily applicable to all couples requesting PGD for CF irrespective of the CFTR variants involved, in line with recently published CF-PGD guidelines. Results: A multiplex PCR protocol was developed including the study of the c.1521_1523del mutation with 12 closely linked polymorphic markers. Preliminary workup was performed for 53 couples and the protocol was clinically applied to 31 couples. All couples were informative for 7-12 markers. Of the 31 couples who initiated a PGD stimulation cycle, 17 couples had a baby. Therefore, the take-home baby rate was 60.7% per couple with an embryo transfer (17 out of 28 couples). Conclusion: This robust, simple, and reliable procedure should allow any couple at risk of transmitting CF to enrol in a PGD programme.